Prevalence of Acute Traumatic Coagulopathy in Acutely Traumatized Dogs and Association with Clinical and Laboratory Parameters at Presentation - Herrero, Yaiza; Jud Schefer, Rahel; Muri, Benjamin M.; Sigrist, Nadja E. (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of this study was to determine the prevalence of acute traumatic coagulopathy (ATC) and identify associated clinical and laboratory parameters including rotational thromboelastometry.Study Design Dogs presenting within 6 hours after trauma were allocated to the ATC or non-ATC group based on thromboelastometry analysis (ex-tem S, in-tem S, fib-tem S). ATC was defined as ≥2 hypocoagulable parameters in 1 profile and ≥ 1 hypocoagulable parameter in an additional profile. Parameters used were ex-tem and in-tem clotting time (CT), clot formation time (CFT), maximum clot firmness (MCF), maximum lysis and fib-tem MCF. Clinical and laboratory parameters at presentation, animal trauma triage (ATT) score, transfusion requirement and outcome were compared. Logistic regression was used to identify independent factors associated with ATC.Results Eleven of 33 dogs presented with ATC and showed ex-tem CT and CFT prolongation and reduced MCF amplitude in all profiles (all p < 0.001). pH (p = 0.043) and potassium concentration (p = 0.022) were significantly lower and bleeding (p = 0.027) and plasma transfusions (p = 0.001) more common in dogs with ATC. Time after trauma (p = 0.040) and Animal Trauma Triage score (p = 0.038, including haematocrit as confounding factor) were associated with the presence of ATC.Conclusion Acute traumatic coagulopathy is more common in traumatized dogs than previously reported. Acute traumatic coagulopathy was associated with acidosis, Animal trauma triage score, time after trauma and higher transfusion needs. Coagulation abnormalities include ex-tem CT and CFT prolongations and decreased clot strength.
Keywords: coagulation; canine; fibrinolysis; ATC; ROTEM